Pengembangan LKPD Representasi Matematis Berbasis Project Based Learning untuk Kelas IV Sekolah Dasar - Nisa, Hani Zakiyatun; Alamsyah, Trian Pamungkas; Firdaus, Firdaus (FARABI: Jurnal Matematika dan Pendidikan Matematika, 2024)
This study aims to determine the development process, product validity, and student response to the development of LKPD Mathematical Representation Based On Project Based Learning For Class IV Elementary Schools. This research uses research and development (R&D) methods using a 4D model consisting of, Define, Design, Development, and Disseminate. Data analysis on is carried out based on expert assessment and learner responses. Data assessment Using Likert scale and Guttman scale. The subject of this study was class IV/B SDN Benda 2 with a total of 20 students for the 2023/2024 school year. The results of this study are in the form of LKPD products PjBL-Based Mathematical Representations for Grade IV Elementary Schools. Validation in product development is seen in terms of material, language, and design with an average score of 88% with the criteria of "very feasible" and can be tested to students. The results of students' responses to LKPD product development obtained a score of 91% with the criterion "very good”. From the results of validation and student response, the PjBL-Based Mathematical Representation LKPD product for Grade IV Elementary School can be said to be very feasible and good for use in learning activities.